2018
DOI: 10.1088/1741-4326/aaf02c
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal modeling of resistive wall mode stability and control in HL-2M tokamak

Abstract: Effects of toroidal plasma flow, magnetic drift kinetic damping as well as feedback control, on the resistive wall mode instability in HL-2M tokamak are numerically investigated, using the linear stability codes MARS-F/K (Liu et al 2000 Phys. Plasmas 7 3681, Liu et al 2008 Phys. Plasmas 15 112503). It is found that the precession drift resonance damping due to trapped thermal particles ensures a robust passive stabilization of the n  =  1 (n is the toroidal mode number) RWM in the 2 MA double-null advanced pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…Figure 1 shows the radial profiles for some key equilibrium quantities. Normalizations for the plasma pressure, current density and toroidal rotation frequency follow that from [42]. The STEP design continues to evolve, and the case studied here represents a particular snapshot during the design process.…”
Section: Equilibrium Specification and Results With Fluid Modelmentioning
confidence: 96%
“…Figure 1 shows the radial profiles for some key equilibrium quantities. Normalizations for the plasma pressure, current density and toroidal rotation frequency follow that from [42]. The STEP design continues to evolve, and the case studied here represents a particular snapshot during the design process.…”
Section: Equilibrium Specification and Results With Fluid Modelmentioning
confidence: 96%
“…Here, β is the plasma pressure normalized by the toroidal magnetic pressure, a = 0.59 m the plasma minor radius, B 0 = 2.2 T the vacuum toroidal magnetic field at the major radius of 1.78 m, and I p = 2 MA the plasma current. Note that the target equilibrium chosen in [44] has 10% higher plasma pressure than Basic geometry of the RWM control on HL-2M: the plasma boundary shape (red solid line) for a 2 MA double-null equilibrium from the high performance scenario, the shape of the conducting vacuum vessel with double-wall structure (blue solid and dashed lines), the locations of the active (black dots) and sensor (red dot) coils. The poloidal angle of the center of the active coils is |θc| = 29.9 • , with the poloidal coverage of ∆θ = 21.8 • .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Previous studies have shown that combination of passive stabilization and active control provides an effective way to suppress the RWM [42][43][44]. In particular, reference [44] investigated the combined effects of toroidal plasma flow, drift kinetic effects from thermal particles, and magnetic feedback on the RWM stability in an HL-2M plasma. Drift kinetic stabilization is ignored in this work, by two reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations